Role of the TATA Binding Protein–Transcription Factor IIB Interaction in Supporting Basal and Activated Transcription in Plant Cells - Pan, Songqin (American Society of Plant Biologists, 2000)
The TATA binding protein (TBP) and transcription factor IIB (TFIIB) play crucial roles in transcription of class II genes. The requirement for TBP–TFIIB interactions was evaluated in maize cells by introducing mutations into the Arabidopsis TBP (AtTBP2) within the C-terminal stirrup. Protein binding experiments indicated that amino acid residues E-144 and E-146 of AtTBP2 are both essential for TFIIB binding in vitro. Activation domains derived from herpes simplex viral protein VP16, the Drosophila fushi tarazu glutamine-rich domain (ftzQ), and yeast Gal4 were tested in transient assays. TBP–TFIIB interactions were dispensable for basal transcription but were required for activated transcription. In general, activated transcription was more severely inhibited by TBP mutation E-146R than by mutation E-144R. However, these TBP mutations had little effect on activity of the full-length cauliflower mosaic virus 35S and maize ubiquitin promoters, thus demonstrating that strong TBP–TFIIB contacts are not always required for transcription driven by complex promoters.